Upaya Pengembangan Kampung TOGA Menjadi Kawasan Edukasi Jamu Berbasis Digital Pada Masyarakat Dusun Umbulrejo Desa Bagorejo Kecamatan Srono Kabupaten Banyuwangi - Nurchayati, Nunuk; As'ari, Hasyim; Qiram, Ikhwanul (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
This PKM or Community Partnership Program is a community service activity aimed at the people of Umbulrejo RT 3 Rw 7 Bagorejo Village, Srono District, Banyuwangi Regency. Partners in this activity are PKK cadres in the area. The purpose of this activity is to help partners develop the TOGA village in the Umbulrejo area into an educational area about traditional medicinal plants and herbs through the digital world. So it is hoped that partners can introduce medicinal plants and herbs as part of Healthy Life Skills and Indonesian Herritage. This activity begins with coordination with partners to synchronize partner needs. Then made a website and android based application with the name Sijamu Digital. The application is intended to help partners learn and teach about TOGA and herbal medicine as well as a vehicle for product promotion. Herbal medicine processing tools are also made by the service team to partners to facilitate the manufacture of herbal medicine effectively and efficiently. Training and mentoring activities are also carried out to help partners make herbal products, namely in the form of gathering comedy, healthy fresh drinks. The evaluation results show that partners play an active role in these activities. The final result of the activity shows an increase in partners' knowledge about traditional medicinal plants, an increase in partners' skills in making products and an increase in product quality. In addition, the results of product sales also show an increase in partner income so that they can increase income during the Covid 19 pandemic.